Transforming rice cultivation in flood prone coastal Odisha to ensure food and economic security - Dar, Manzoor H.; Chakravorty, Ritadhi; Waza, Showkat A.; Sharma, Mayank; Zaidi, Najam W.; Singh, Amrendra N.; Singh, Umesh S.; Ismail, Abdelbagi M. (Springer, 2017)
Flash floods leading to complete submergence of rice plants for 10–15 days is one of the major constraints for rice production, mainly in rainfed lowland areas. In India, 30% of the rice growing area (12–14 M ha) is prone to flash flooding with average productivity of only 0.5–0.8 t ha−1. Coastal Odisha is one of the most flood prone areas of India where the paddy crop in the wet season is often devastated by flash floods, forcing farmers either to discontinue paddy cultivation or to revert to traditional varieties with very low yields. The flood tolerant variety, Swarna-Sub1 (SS1), was introduced through cluster demonstrations in some villages of the Bari block of Odisha in 2013. SS1 seeds were provided to 355 farmers in two villages affected by floods twice in 2013. The majority of the farmers cultivated SS1 in 2013 and about 75% of them persisted with the variety in 2014. There has been a steady and significant increase in paddy cultivation and yields per unit area between 2012 and 2014 and a sharp increase in paddy sales during 2013 and 2014. The present study showed that farmers preferred to cultivate low yielding traditional land races owing to their better flood tolerance and the unavailability of flood tolerant high yielding varieties (HYVs). Traditional varieties gave 30–42% higher yields than non-SS1 HYVs when flooding occurred. SS1 on the other hand offered a significant yield advantage of about twice that of traditional varieties, in both flooding and non-flooding years. There is an additional social advantage of SSI in that famers belonging to scheduled castes in flood prone villages, have greater numbers of plots that are exposed to prolonged floods. Thus they benefit proportionately more from the introduction of SS1